Impact of Hormonal Therapies for Treatment of Hormone-Dependent Cancers (Breast and Prostate) on the Cardiovascular System: Effects and Modifications. (June 2021) - Okwuosa, Tochi M.; Morgans, Alicia; Rhee, June-Wha; Reding, Kerryn W.; Maliski, Sally; Plana, Juan-Carlos; Volgman, Annabelle Santos; Moseley, Kendall F.; Porter, Charles B.; Ismail-Khan, Roohi
Abstract : Cardiovascular disease and cancer are the leading causes of death in the United States, and hormone-dependent cancers (breast and prostate cancer) are the most common noncutaneous malignancies in women and men, respectively. The hormonal (endocrine-related) therapies that serve as a backbone for treatment of both cancers improve survival but also increase cardiovascular morbidity and mortality among survivors. This consensus statement describes the risks associated with specific hormonal therapies used to treat breast and prostate cancer and provides an evidence-based approach to prevent and detect adverse cardiovascular outcomes. Areas of uncertainty are highlighted, including the cardiovascular effects of different durations of hormonal therapy, the cardiovascular risks associated with combinations of newer generations of more intensive hormonal treatments, and the specific cardiovascular risks that affect individuals of various races/ethnicities. Finally, there is an emphasis on the use of a multidisciplinary approach to the implementation of lifestyle and pharmacological strategies for management and risk reduction both during and after active treatment. Abstract : Supplemental Digital Content is available in the text.